Selecting Names for Experiments on Ethnic Discrimination - Stijn Baert; Louis Lippens; Hannah Van Borm (Institute of Labor Economics (IZA), 2022)
In recent decades, researchers have found compelling evidence of discrimination in the labor and housing market toward ethnic minorities based on field experiments using fictitious applications. However, these findings may be exaggerated as the names used for ethnic minorities in various experiments may have also signaled low socioeconomic class. Therefore, in this study, we perform a name categorization experiment in the United States that yields 56 names associated with six ethnicity groups, which signal different ethnicities and genders but similar social classes. These names should greatly improve the validity of future experiments on ethnic discrimination.
Keywords: C91; C93; J71; 330; ethnic discrimination; social class; experiments